Optical properties of Al-CdO nano-clusters thin films - Yahia, I. S.; Salem, G. F.; Abd El-sadek, M. S.; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2013)
The aluminum doped cadmium oxide (CdO:Al) thin films were grown onto glass substrates by sol-gel spin-coating method. The structural properties of undoped and Al-doped CdO thin films were studied by atomic force microscopy. AFM results reveal that the studied CdO films were formed from the nano-clusters. The optical transmittance of undoped and Al-doped CdO is decreased with increasing Al contents. The optical band gaps of the CdO films were varied from 2.54 eV to 2.32 eV with increasing Al dopants. The width of localized states in the optical band gap of the films is increased with increasing Al content. The improvement of the optical constant of Al-doped CdO has potential applications as transparent conducting oxide for different optoelectronic device applications. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Thin films; Sol-gel growth; Electron microscopy; Optical properties